Planning and the environment - Clinch, J. Peter (Centre for Urban and Regional Studies. Trinity College Dublin, & the Faculty of the Built Environment, Dublin Institute of Technology. Bolton Street, 2004)
This paper discusses the relationship between planning, sustainable development and the environment in Ireland. The paper firstly explores the development of planning as a Concept. It then sets out the key 'actors' in Irish environmental policy. The paper goes on to describe the planning system in Ireland with a specific emphasis on its relationship to sustainable development and the environment. Irish environmental performance is assessed. Irish environmental policy 'drivers' are then examined with a view to explaining the emphasis of Irish environmental policy. The paper demonstrates and explains the lack of influence of the planning system on key areas of environmental policy but emphasises its importance in addressing, in particular, urban and suburban environmental problems. The paper identifies the following impediments to the effective operation of tile planning system in enhancing sustainable development: lack of consistency in government policy and legislation as regards sustainable development; poor public perception of planning and the role of political system therein; limited policy instruments and the emphasis on regulation; and lack of research for evidence-based policymaking.
Keywords: Urban geography -- Ireland